The Poetic and Odorocolophonic Dimensions of Aitmatov’s Jamilia and their Transformation in Uzbek Translation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article explores the phonostylistic and odorocolophonic dimensions of Chingiz Aitmatov’s novella Jamilia (1958), originally titled Obon (“Melody”) in Kyrgyz. Through a comparative analysis of the Russian original and its Uzbek translation by A. Rashidov, the study examines how musicality, color symbolism, and olfactory imagery form the core of Aitmatov’s poetics. It argues that Aitmatov’s artistic system-rooted in the interconnection of sound, scent, and visual rhythm-constructs a synesthetic narrative that transcends traditional realism. The paper demonstrates that deviations in the Uzbek translation, such as lexical expansions and syntactic alterations, disrupt the delicate odorocolophonic balance of the original. Emphasis is placed on the author’s unique synthesis of auditory and visual motifs, which transform Jamilia into a lyrical and symbolic composition.